Taste alteration, mouth dryness and teeth staining as side effects of medications taken by elderly - de Deco, Camila Porto [UNESP]; Reis, Michelle Roberta Vieira Silva; Marchini, Adriana Mathias Pereira da Silva [UNESP]; da Rocha, Rosilene Fernandes [UNESP]; dos Santos, Mateus Bertolini Fernandes; Marchini, Leonardo (My University, 2014)
Elderly patients generally use several types of medication, some of which may cause oral side effects. Aim: To investigate the oral side effects caused by medication in an elderly sample. Methods: Three hundred patients were interviewed about their use of medication and were divided in two groups: institutionalized (n=150) and community-dwelling (n=150) elderly. Results: The most used drugs were antihypertensives (53%) for community-dwelling elders and antiulceratives (76%) for the institutionalized ones. The more prevalent side effects were taste alterations that occurred in 19%, dry mouth in 17% and teeth staining in 2%. Conclusions: A high prevalence of oral side effects from medications used by the elderly was found in this study. The health professionals should be aware of the possible side effects caused by prescribed medications.
Keywords: Aged; Drug interactions; Xerostomia